Analisis Efektivitas Dan Kontribusi Pajak Daerah Sebagai Sumber Pendapatan Asli Daerah (Studi Pada Bapenda Dki Jakarta Tahun 2016-2020) - Lulu Lovianna; Notika Rahmi (Jurnal Pajak Vokasi (JUPASI), 2022)
This study aims to determine the level of effectiveness and contribution of local taxes as a source of locally-generated revenue (PAD), the obstacles faced during implementation, and the efforts made to overcome these obstacles. Research data includes primary and secondary data which were analyzed using qualitative descriptive methods. The results of this study indicate that the level of effectiveness of local taxes as a source of PAD is the ‘effective’ category with an average value of 97.19%, and the level of contribution of local taxes as a source of PAD is classified as ‘very good’ with an average value of 85.80%. However, in the realization of this effort, obstacles were found, including the low awareness of taxpayers